Strategi Optimalisasi Smart Economy Dalam Peningkatan Daya Saing UMKM Di Kota Bandung - Hariyatna Syaeful Umam; Ade Yunita Mafruhat (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2022)
The purpose of this study is to analyze how to optimize the smart economy in empowering MSMEs in order to increase MSMEs competitiveness in the city of Bandung. The type of research used is descriptive research with a qualitative approach. The results of this study, the Bandung City government already has a strategy in optimizing the smart economy in empowering MSMEs, it is well seen that there are many actors who have taken part in the implementation of the smart economy program. Through a SWOT analysis, quadrant I shows the position of the MSMEs optimization strategy and the S-O strategy position is used, namely utilizing the image of the City of Bandung as a city with smart economy and government support to increase the competitiveness of MSMEs.